History and Correlates of Smoking Cessation Behaviors Among Individuals With Current or Past Major Depressive Disorder Enrolled in a Smoking Cessation Trial. Issue 1 (14th July 2021) - Quinn, Mackenzie Hosie; Olonoff, Matthew; Bauer, Anna-Marika; Fox, Erica; Jao, Nancy; Lubitz, Su Fen; Leone, Frank; Gollan, Jacqueline K; Schnoll, Robert; Hitsman, Brian
Abstract: Introduction: Smoking among adults with major depressive disorder (MDD) is at least double that of the general US population. More effective smoking cessation interventions for depressed smokers may be facilitated through a better understanding of the smoking and depression-related characteristics of this population. Methods: We used baseline data from 300 participants enrolled in randomized clinical trial for smokers with current or past MDD. We described history of smoking cessation behaviors (ie, quit attempts, quit motivation, and cessation treatment utilization) and used multivariate regression to identify demographic and depression-related correlates of these behaviors. Results: Sixty-eight percent of participants reported at least one quit attempt in the past year, nearly 51% reported motivation to quit in the subsequent 30 days, and 83% reported prior use of a nicotine replacement therapy. A greater readiness to quit smoking was associated with increased age ( p = .04) and lower cigarettes per day ( p = .01). Greater use of smoking cessation medication was associated with greater education and nicotine dependence, minority race, and greater use of complementary reinforcers (eg, activities associated with increased reinforcing value of smoking; p 's < .05). Conclusions: These data indicate that smokers with current or past MDD are highly motivated to quit smoking and have a history of engaging in efforts to quit. Interventions to promote smoking cessation behaviors should address younger and lighter smokers, who may perceive less risk from tobacco use, and efforts to promote smoking cessation medications and counseling should address minority smokers who are engaging in complementary reinforcers. Implications: These data are inconsistent with the assumption that smokers with serious mental illness are not willing to quit smoking and suggest the need for studies that test behavioral interventions that address complementary reinforcers to treat tobacco use in this community.